Antibody drug conjugates (ADCs) charged with HDAC inhibitor for targeted epigenetic modulation. Issue 31 (10th July 2018) - Cini, Elena; Faltoni, Valentina; Petricci, Elena; Taddei, Maurizio; Salvini, Laura; Giannini, Giuseppe; Vesci, Loredana; Milazzo, Ferdinando Maria; Anastasi, Anna Maria; Battistuzzi, Gianfranco; De Santis, Rita
Abstract : A new weapon is added to the ADC arsenal, a thiol based HDAC inhibitor. Low toxic, hits the target and stops tumor growth in many mouse models. Abstract : We describe here two novel antibody-drug conjugates loaded with the HDAC inhibitor ST7612AA1 (IC50 equal to 0.07 μM on NCI-H460 cells), a thiol-based molecule with a moderate toxicity in vivo . Two payloads were prepared using cleavable and non-cleavable linkers. After anchoring to cetuximab through amide bond with lysines, the resulting HDAC inhibitor-antibody conjugates showed ability to recognize EGFR and efficient internalization in tumor cells. Both ADCs induced sensible increment of histones 3 and 4 and alpha-tubulin acetylation. Animal models of human solid tumors showed high anti-tumor efficacy of the conjugates without the toxicity generally observed with traditional ADCs delivering highly potent cytotoxic drugs. These compounds, the first ADCs charged with not highly cytotoxic warheads, are potentially suitable for epigenetic modulation, extending the ADC strategy to the targeted delivery of HDAC inhibitors with many possible therapeutic applications beyond cancer.